Beyond Black and White: an Analysis of Newspaper Representations of Alleged Criminal Offenders Based on Race and Ethnicity - Colburn, Alayna (Journal of contemporary criminal justice, 2018)
Media has a substantial role in providing knowledge about crime to the public; however, many representations of crime and criminality perpetuate damaging racial stereotypes. The purpose of this study is to identify how minorities are portrayed in print media as compared to their White counterparts. The study includes an ethnographic content analysis of newspaper crime stories and accompanying images from widely circulated newspapers published between August 1, 2014, and October 31, 2014. Findings reveal minorities are not only overrepresented in crime story images, but closer examination uncovers nuanced differences in the type and quality of pictures by race and ethnicity.